Integrating network pharmacology, in silico molecular docking and experimental validation to explain the anticancer, apoptotic, and anti-metastatic effects of cosmosiin natural product against human lung carcinoma - Gu Qin; Pan Xiaofei; Ding Hui; He Yuan; Liu Kan (Türk Biyokimya Dergisi)
This research aimed to examine the anticancer properties of cosmosiin, a natural flavonoid, on human lung carcinoma cells by in silico molecular docking, network pharmacology, and in vitro experiments.